Factors influencing customer's brand loyalty o f ILA language center in Hanoi - Ngo, Thi Mai (H. : ĐHQGHN, 2020)
This study examined the situation of ILA English centers. Based on the results of a customer survey, the study identified that quality of brand, brand satisfaction level played a very important role in making ILA customers as loyal customers. It was also proved by survey results that brand communication perceived price and promotion are also important factors that could influence ILA’s brand loyalty. During the analysis of finding, it was observed that barriers like switching cost did not play a great role in forcing the ILA customer to continue to be loyal to their English centers. Findings and analysis result further also showed that more than half of these people were committed to ILA brand, describing their current brand as their first choice. Moreover, after analysis of the findings and related theories, it was established that well over half of the people interviewed were loyal to ILA English centers.